2012
DOI: 10.1111/j.1095-8649.2012.03360.x
|View full text |Cite
|
Sign up to set email alerts
|

Dead fish swimming: a review of research on the early migration and high premature mortality in adult Fraser River sockeye salmon Oncorhynchus nerka

Abstract: Adult sockeye salmon Oncorhynchus nerka destined for the Fraser River, British Columbia are some of the most economically important populations but changes in the timing of their homeward migration have led to management challenges and conservation concerns. After a directed migration from the open ocean to the coast, this group historically would mill just off shore for 3-6 weeks prior to migrating up the Fraser River. This milling behaviour changed abruptly in 1995 and thereafter, decreasing to only a few da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 51 publications
7
145
0
Order By: Relevance
“…Studies using biotelemetry to study survival, behavior (e.g., entry timing, migration speed), and physiology (e.g., tissue samples of telemetered animals, parallel laboratory cardiorespiratory studies) reveal that there are stock-specific thermal thresholds and clear relationships between impaired migration behavior (including failed migration and subsequent death) and physiological status Hinch et al 2012). The cardiorespiratory capacity of Pacific salmon is constrained such that fish are unable to migrate beyond a given stock-specific thermal threshold Eliason et al 2011).…”
Section: Pacific Salmon (Oncorhynchus Spp) and Climate Changementioning
confidence: 99%
“…Studies using biotelemetry to study survival, behavior (e.g., entry timing, migration speed), and physiology (e.g., tissue samples of telemetered animals, parallel laboratory cardiorespiratory studies) reveal that there are stock-specific thermal thresholds and clear relationships between impaired migration behavior (including failed migration and subsequent death) and physiological status Hinch et al 2012). The cardiorespiratory capacity of Pacific salmon is constrained such that fish are unable to migrate beyond a given stock-specific thermal threshold Eliason et al 2011).…”
Section: Pacific Salmon (Oncorhynchus Spp) and Climate Changementioning
confidence: 99%
“…Within this paradigm of local adaptation, it is perhaps not surprising that the ever-increasing peak summer temperatures of the Fraser River, British Columbia, Canada, superimposed on normal annual variability, have caused high en route mortality in sockeye salmon in some years (Patterson et al, 2007;Farrell et al, 2008;Martins et al, 2011;Hinch et al, 2012). Consequently, understanding the underlying cause(s) of migration failure at high temperatures will be fundamental to efforts aimed at conserving the diversity of wild Pacific salmon.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, understanding the underlying cause(s) of migration failure at high temperatures will be fundamental to efforts aimed at conserving the diversity of wild Pacific salmon. Indeed, a progressive decline in AS above historic modal river temperatures has been proposed as one of several potential mechanisms for population-specific en route mortality at high temperatures Hinch et al, 2012). With climatic change occurring at an alarming rate and regarded as a key pressure acting upon Pacific salmon conservation and management (Patterson et al, 2007;Crozier et al, 2008;Bryant, 2009;Martins et al, 2011;Reed et al, 2011), AS has emerged as a potentially useful functional measurement with which to make predictions about the thermal niche of aquatic ectotherms and hence potential fitness outcomes under future warming scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Initial scientific analyses indicated the long-term decline in abundance was likely associated with a decline in productivity at sea rather than low parental spawner abundances or other factors in fresh water. Factors in fresh water are known to adversely impact Fraser sockeye salmon (e.g., Hinch et al 2012), but the observed long-term decline in productivity could not be explained by freshwater processes alone Connors et al 2012). Recently, a number of investigations have explored early marine factors associated with the unexpectedly small sockeye salmon return in 2009 (Rensel et al 2010;Miller et al 2011;Beamish et al 2012; Thomson et al 2012;McKinnell et al 2014).…”
Section: Introductionmentioning
confidence: 99%